Symbols and Its Role in the Quranic Stories - Hasan Kharaghani; Ali Khayyat; Muhammad Zaher Ghorbani (آموزه‌های قرآنی, 2022)
The holy Quran has drawn the spiritual and abstract concepts with the use of the symbol in a form of the material structures and creates dynamic and effective images in the addresses’ mind and it influences on human minds. One of the differences of the Quranic stories with other human stories is compatibility and meta-time modeling. The story of hazrat Musa (Moses) (p.b.u.h) as the most extensive Quranic tale contains the highest use of symbols. The function of the symbol is one the factors of the creating dynamic and compatibility and meta-time modeling of this story as the inward feelings and thought of the addresser has drawn attention to it during the history and it has attracted and allured him. Meanwhile studying whatness of the symbol this research answers this question how the function of the symbol in the story of hazrat Musa (Moses) (p.b.u.h) has made this story to be meta-time and it studies the stick being the symbol of displaying power, the Samiri calf being the symbol of deviance, Israelites’ complaints (grips) being the symbol of complaining and stubbornness, Asiya being the symbol of self-control and it defines the pharaoh of the exodus, Haman and Korah as three invalid (falsehood/ void) symbols of the political, religious (belief) and economic fronts.